ANALISIS MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR AND SHARE (TPS) TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPAS (ILMU PENGETAHUAN ALAM DAN SOSIAL) KELAS IV DI GUGUS 3 JANGKAR TAHUN AJARAN 2024/2025 - Puspitaningtyas, Amalia Risqi; Erinda Nur Kharimah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to analyze the impact of implementing the Think Pair and Share model in science learning (IPAS) for fourth-grade students in Cluster 3 Jangkar. The research subjects consisted of SD Negeri 1 Kumbangsari as the control group and SD Negeri 2 Kumbangsari as the experimental group. The study employed a Quasi-Experimental method with a Post-Test Only design. The results showed that the use of the Think Pair and Share model had a positive effect on students' learning outcomes in the material of changes in the state of matter in science lessons. Based on the normality test, the data were normally distributed with a significance value of 0.200 for the experimental group post-test and 0.094 for the control group post-test. The homogeneity test showed that the data were homogeneous, with a significance value of 0.623 based on the mean. The t-test results indicated a significance value (2-tailed) of 0.000, meaning H0 was rejected, and H1 was accepted. Therefore, it can be concluded that the use of the Think Pair and Share model significantly affects the learning outcomes of fourth-grade science students in Cluster 3 Jangkar.